Antagonistic Potential of Fluorescent Pseudomonads Colonizing Wheat Heads Against Mycotoxin Producing Alternaria and Fusaria - Müller, Thomas; Ruppel, Silke; Behrendt, Undine; Lentzsch, Peter; Müller, Marina E. H. (Frontiers in Microbiology, 2018)
Natural control of phytopathogenic microorganisms is assumed as a priority function of the commensal plant microbiota. In this study, the suitability of fluorescent pseudomonads in the phyllosphere of crop plants as natural control agents was evaluated. Under field conditions, ears of winter wheat were found to be colonized with high consistency and at a high density by pseudomonads at the late milk dough stage. Isolates of these bacteria were evaluated for their potential to protect the plants from phytopathogenic Alternaria and Fusarium fungi. More Pseudomonas isolates were antagonistically active against alternaria than against fusaria in the dual culture test. The alternaria responded species-specifically and more sensitively to bacterial antagonism than the strain-specific reacting fusaria. A total of 110 randomly selected Pseudomonas isolates were screened for genes involved in the biosynthesis of the antibiotics 2,4-diacetylphloroglucinol, phenazine-1-carboxylic acid, pyoluteorin, and pyrrolnitrin. The key gene for production of the phloroglucinol was found in none of these isolates. At least one of the genes, encoding the biosynthesis of the other antibiotics was detected in 81% of the isolates tested. However, the antagonistic effect found in the dual culture assay was not necessarily associated with the presence of these antibiotic genes. Wheat grains as natural substrate were inoculated with selected antagonistic Pseudomonas isolates and Alternaria and Fusarium strains, respectively. The fungal growth was only slightly delayed, but the mycotoxin production was significantly reduced in most of these approaches. In conclusion, the distribution of phytopathogenic fungi of the genera Alternaria and Fusarium in the field is unlikely to be inhibited by naturally occurring pseudomonads, also because the bacterial antagonists were not evenly distributed in the field. However, pseudomonads can reduce the production of Alternaria and Fusarium mycotoxins in wheat grains and thus have the potential to improve the crop quality.